Case study of pipeline failure analysis from two automated vacuum collection system. (1st May 2021) - Farré, J.A.; Salgado-Pizarro, R.; Martín, M.; Zsembinszki, G.; Gasia, J.; Cabeza, L.F.; Barreneche, C.; Fernández, A.I.
Highlights: 90% of failures in two AWCS plants were originated by the abrasive at attrition. Waste glass content and transportation rate are key factors affecting the failure. Key design aspects: elbows' radius of curvature and junctions of straight sections. Abstract: Conventional municipal waste management systems based on collecting and storing waste for future management are cost-effective and flexible. These systems present significant problems such as odours, plagues and hygiene problems caused by their storage and greenhouse gas emissions from garbage trucks used for the transport of waste. The Automated Waste Collection System (AWCS) and Automated Vacuum Waste Collection (AVWC) systems, in which waste is transported directly underground to the processing plants, are efficient collection systems and respectful of the environment as alternatives to traditional systems. The pneumatic system reduces the value of the per capita generation of general waste. The present study explains the origin of pipe failure in two different AWCS factories, as well as the identification of the failure phenomena. To carry out the study, a classification of 90 failure cases by primary cause was performed, followed by recommendations to avoid these failures in the future. Moreover, a computational fluid dynamics (CFD) simulation was performed in order to help in the failure determination and the key recommendations to avoid the most common and frequent failures.